The Efficacy of Some Plants Extracts on Fallarmyworm (Spodopterafrugiperda, J.E. Smizh) in Sudan - Elsheikh M. Kona Nada; AwadKhalafallaTaha; Mohamed Adam AbubakerHaroun; E. E. Mahmoud Mohammed (Journal of Agronomy Research, 2021)
The Fall armyworm worm (FAW) (Spodopterafrugiperda) is one of the important economic pests which goes on several field crops and causes serious damage. The aim of this study was to look for efficient, less cost and environmentally friend plant extract for controlling Fall armyworm worm in cereal crops. A Complete Randomized Block Design (CRBD) experiments with three replications were conducted in the laboratory to investigate the insecticidal effects of four plant extracts consisting of ethanolic extract of Neem (Azadirachta indica) seeds, Black pepper (Piper nigrum) seeds, Usher (Calotropis procera ) leaves and water extracts of Argel (Solenostemma argel) leaves on larvae of the Fall armyworm (FAW) (Spodoptera frugiperda). Newly emerged larvae of FAW were treated topically by 4 concentrations (10, 25, 50 and 75%) of each extract, and then the larval mortalities were calculated after 24, 48 and72 hrs. The results showed the highest concentrations (75%) of the three ethanolic extracts gave higher mortality percentages (100%) after 72 hrs of exposure, compared with other concentrations. Also, these were not significantly different from the recommended dose of the standard pesticide “Spinosad”. On the other hand, Argel water extract showed no effect on the (FAW) larvae. It is recommended that this experiment to be replicated under different environments.
Keywords: Argel